Liraglutide in people treated for type 2 diabetes with multiple daily insulin injections: randomised clinical trial (MDI Liraglutide trial). (28th October 2015) - Lind, Marcus; Hirsch, Irl B; Tuomilehto, Jaakko; Dahlqvist, Sofia; Ahrén, Bo; Torffvit, Ole; Attvall, Stig; Ekelund, Magnus; Filipsson, Karin; Tengmark, Bengt-Olov; Sjöberg, Stefan; Pehrsson, Nils-Gunnar
Abstract : Study question What are the effects of liraglutide, an incretin based treatment, on glycaemic control in people with type 2 diabetes treated with multiple daily insulin injections? Methods The study was a randomised, double blind, placebo controlled trial with a parallel group design carried out at 13 hospital based outpatient clinics and one primary care unit in Sweden. Patients were considered eligible for inclusion if they had type 2 diabetes and inadequate glycaemic control (HbA1c concentrations ≥58 mmol/mol (7.5%) and ≤102 mmol/mol (11.5%)), a body mass index of 27.5-45 kg/m 2, and required multiple daily insulin injections. Overall, 124 participants were randomised 1:1 to subcutaneous liraglutide or placebo by minimisation allocation. The main outcome measure was change in HbA1c level from baseline to week 24. Study answer and limitations Liraglutide was associated with a significant reduction of 16.9 mmol/mol (1.5%) in HbA1c versus 4.6 mmol/mol (0.4%) for placebo, difference −12.3 mmol/mol (95% confidence interval −15.8 to −8.8 mmol/mol; −1.13%, −1.45 to −0.81 mmol/mol). Body weight was significantly reduced in participants in the liraglutide compared with placebo group (3.8 v 0.0 kg, difference −3.8, −4.9 to −2.8 kg), and total daily insulin doses were significantly reduced, by 18.1 units and 2.3 units (difference −15.8, −23.1 to −8.5 units). Reductions in mean and standard deviation of glucose levels estimated by masked continuous glucose monitoring were significantly greater in the liraglutide group than placebo group (−1.9 and −0.5 mmol/L). Neither group experienced severe hypoglycaemic events nor were there any significant differences in symptomatic or asymptomatic non-severe hypoglycaemia (<4.0 or <3.0 mmol/L). The mean number of non-severe symptomatic hypoglycaemic events (<4.0 mmol/L) during follow-up was 1.29 in the liraglutide group and 1.24 in the placebo group (P=0.96). One of the study's limitations was its relatively short duration. Sustained effects of liraglutide have, however, been found over lengthier periods in connection with other treatment regimens. Cardiovascular safety and potential adverse events during longer exposure to liraglutide need to be evaluated. Nausea was experienced by 21 (32.8%) participants in the liraglutide group and 5 (7.8%) in the placebo group and 3 (5%) and 4 (7%) participants in these groups, respectively, had any serious adverse event. What this study adds Adding liraglutide to multiple daily insulin injections in people with type 2 diabetes improves glycaemic control without an increased risk of hypoglycaemia, reduces body weight, and enables patients to lower their insulin doses. Funding, competing interests, data sharing This study was an investigator initiated trial, supported in part by Novo Nordisk and InfuCare. Potential competing interests have been reported and are available on thebmj.com. Study registration EudraCT 2012-001941-42.